Loop corrections to supergravity on AdS(5) x S^5 - Alday, L; Bissi, A (American Physical Society, 2017)
We consider the four-point correlator of the stress-energy tensor multiplet in N=4 super Yang-Mills theory. In the planar limit and at large 't Hooft coupling, such a correlator is given by the corresponding holographic correlation function in IIB supergravity on AdS5×S5. We consider subleading corrections in the number of colors, i.e., order 1/N4, at large 't Hooft coupling. This corresponds to loop corrections to the supergravity result. Consistency conditions, most notably, crossing symmetry, constrain the form of such corrections and lead to a complete determination of the spectrum of leading-twist intermediate operators.